Intensive plant productions - “Proalim Km 0”, in times of a Covid-19 pandemic – Part 1. Predisposition of consumers of vegetables, fruits and medicinal aromatics to their production, agribusiness and consumption - Bellaccomo, Maria Carolina; Berriolo, Maria Jimena; Caracotche, Maria Veronica; Castagnino, Ana María; Cendon, Maria Laura; Díaz, K.E.; Gonzalez Ferrin, Maria Soledad; Martinoia, G.I.; Mairosser, Andrea; Rogers, W.J.; Villagra, Constanza Marcela; Zazzetta, Malvina Lis (Asociación Argentina de Horticultura, 2021)
Given the importance that, for the health of the population, an adequate consumption of products of plant origin has, and in order to have a diagnosis on the intensive vegetable production of healthy foods (PVIAS) of proximity, at the level of urban family gardens and of commercial ventures, their production, processing, marketing and consumption preferences, in the current socio-economic and productive context, an inter-institutional survey called “ProALIM Km 0” was carried out. It was organized within the framework of the inter-institutional project CIAC-940186 (INTA – AUDEAS – CONADEV) “Intensive Vegetable Productions of Healthy Foods - PVIAS”, using Google form (Google Forms). The main objective of this work to know the habits, preferences and changes produced in the population, regarding the production, agroindustry and / or consumption of vegetables, fruits and medicinal aromatics (intensive vegetable productions - PVIAS), in the current socio-economic and productive context. The surveyed population demonstrated to know and have interest in the production, agribusiness and consumption of PVIAS, and it was detected that, in many cases, this interest is not specified in practice, especially in relation to the consumption of vegetables and water, in the that reality is, to a great extent, far from national and international recommendations. These differences would indicate that, from the institutions, actions must be carried out that make it possible to translate into practice, aspects that the population knows of their convenience.